Tissue-resident CD8 T cells in central nervous system inflammatory diseases: present at the crime scene and …guilty. (August 2022) - Merkler, Doron; Vincenti, Ilena; Masson, Frederick; Liblau, Roland S
Abstract : Tissue-resident memory T cells (TRM ) represent a subset of antigen-experienced T cells that are constantly retained in a given tissue with limited trafficking through the circulation. These cells are characterized by expression of molecules enabling their tissue anchoring and downregulation of molecules promoting tissue egress. They reside at sites of previous antigen encounter and their number increases with age. TRM have been shown to provide rapid and efficient protection against tissue reinfection and TRM density correlates with efficient antitumor responses. Intriguingly, the density of CD8 TRM is increased in the central nervous system (CNS) of patients with neuroinflammatory diseases such as multiple sclerosis, or suffering from neurodegenerative diseases. In this review, we discuss current knowledge regarding the diversity of CNS-resident CD8 T cells and their role in CNS autoimmunity. Given their likely contribution to the protracted course of several inflammatory diseases of the CNS, their therapeutic targeting becomes an important challenge.